A Methodological Framework for Prioritizing Infrastructure Investment - Andres, Luis; Biller, Dan; Herrera Dappe, Matias (World Bank, Washington, DC, 2015)
Policy makers are often confronted with a myriad of factors in the investment decision-making process. This issue is particularly acute in infrastructure investment decisions, as these often involve significant financial resources and lock-in technologies. In regions and countries where the infrastructure access gap is large and pubic budgets severely constrained, the importance of considering the different facets of the decision-making process becomes even more relevant. This paper discusses the trade-offs policy makers confront when attempting to prioritize infrastructure investments, in particular with regard to economic growth and welfare, and proposes a methodological framework for prioritizing infrastructure projects and portfolios that holistically equates such trade-offs, among others. The analysis suggests that it is not desirable to have a single methodology, providing a single ranking of infrastructure investments, because of the complexities of infrastructure investments. Rather, a multidisciplinary approach should be taken. Decision makers will also need to account for factors that are often not easily measured. While having techniques that enable logical frameworks in the decision-making process of establishing priorities is highly desirable, they are no substitute for consensus building and political negotiations.